Acrylate‐based photosensitive resin for stereolithographic three‐dimensional printing. Issue 21 (23rd January 2019) - Zhang, Xueqian; Xu, Yu; Li, Lei; Yan, Bei; Bao, Jianjun; Zhang, Aiming
ABSTRACT: In this article, we report an acrylate‐based three‐dimensional (3D) printing stereolithography rapid‐prototyping photosensitive resin with a low viscosity, small volumetric shrinkage, high photoreactivity, and excellent strength. The resin was a compound prepared with bisphenol A epoxy acrylate (BAEA) as the main matrix, 1, 6‐hexanediol diacrylate (HDDA) and tri(propylene glycol) diacrylate (TPGDA) as reactive diluents, pentaerythritol triacrylate (PETA) as the crosslinking agent, and 2‐hydroxy‐2‐methyl propiophenone (1173) and diphenyl(2, 4, 6‐trimethyl benzoyl)phosphine oxide (TPO) as photoinitiators. The photocuring kinetics of the resins with different photoinitiator types and loadings were studied via real‐time IR spectroscopy, which provided insights into the optimization of photoinitiator composition and printing parameter settings. The results show that the content change of each component affected the viscosity of the photosensitive resin; this was accompanied by fluctuations in the volume shrinkage and mechanical strength of the cured products. Although an increase in the molar ratio of the reactive diluent remarkably reduced the viscosity of the photosensitive resin and thereby boosted photopolymerization, it also caused an increase in the volume shrinkage and a sacrifice of mechanical strength. Finally, as shown by a comparison of the other samples we studied, the resin composed of 30 mmol HDDA, 50 mmol TPGDA, 10 mmol PETA, 10 mmol BAEA, 2.5 mol % TPO, and 2.5 mol % 1173 achieved the best viscosity of 239.53 mPa s at 25 °C, the minimum shrinkage rate of 4.36%, and the maximum tensile strength of 43.19 MPa. The 3D printing curing products had the closest size to the design dimensions of the computer‐aided design model; this indicated that the resin seemed to be a most promising candidate for 3D printing applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47487. Abstract :